Leisure Time Physical Activity in Relation to Mortality Among African American Women - Li, Shanshan (Am J Prev Med, 2020)
INTRODUCTION: African American women have a life expectancy 2.7 years shorter than that of white women and are less likely than white women to meet national physical activity guidelines. Physical activity has been found to reduce mortality, but evidence concerning African American women is limited. METHODS: In the Black Women’s Health Study, a prospective cohort study of African American women begun in 1995, a total of 52,993 participants who were free of cardiovascular disease and cancer at enrollment were followed through 2017. Cox proportional hazards models evaluated the associations of repeated measures of physical activity with mortality, adjusting for demographic, medical, and lifestyle factors. Statistical analyses were last performed in September 2019. RESULTS: During 22 years of follow-up, 4,719 deaths occurred. Higher levels of physical activity were associated with reduced all-cause, cardiovascular disease, and cancer mortality. Hazard ratios for walking ≥5 hours/week relative to no walking were 0.69 (95% CI=0.62, 0.77), 0.71 (95% CI=0.57, 0.87), and 0.80 (95% CI=0.67, 0.96) for all-cause, cardiovascular disease, and cancer mortality, respectively. The comparable hazard ratios for vigorous exercise for ≥5 hours/week versus none were 0.58 (95% CI=0.50, 0.67), 0.66 (95% CI=0.50, 0.87), and 0.52 (95% CI=0.39, 0.72). CONCLUSIONS: Both walking for exercise and vigorous exercise were associated with reductions in mortality among African American women, including deaths from cardiovascular disease and deaths from cancer, both of which are disproportionately high in the African American population. These findings underline the importance of institutional and individual changes that will lead to increased physical activity.